Comparative Effectiveness of Self-Instructional Print Media and Conventional Teaching Method on Secondary School Students Achievement in Physics in Osun State - Olaniyi, Oluseyi Abraham; Hassan, Moshood Ayinde (American International Journal of Social Science Research, 2019)
The current decline in the performance of secondary school students in Physics in the Senior School Certificate Examination (SSCE) has become a major concern for the stakeholders in the field of education. This may perhaps, be partly due to the strict adherence of Physics teachers to the use of conventional teaching method in teaching Physics. This study was therefore carried out with the aim of evaluating the comparative effectiveness of Self-instructional Print Media and the conventional teaching method on secondary school students’ achievement in Physics in Osun State. A non-randomised control group pretest-posttest quasi-experimental research design was adopted for the study. Self-Instructional Printed Material in Physics (SIPMP), Lesson Plan in Physics (LPP), Entry Behaviour Test in Physics (EBTP) and Achievement Test in Physics (ATP) were the research instruments used in this study. One hundred and seventy three (173) SSS II students from six intact classes of six purposively selected secondary schools in Osun State constituted the sample of the study. These students were randomly assigned into the three quasi-experimental groups, namely: Self-instructional Print Media alone (SIPM alone), Self-instructional Print Media with the conventional Teaching Method (SIPM with CTM) and the Conventional Teaching Method alone (CTM alone). The three groups were tested prior to and after their exposure to the experimental treatment. The data collected were analysed to answer the five research questions and test the four hypotheses raised for the study using mean scores, t-test, ANOVA and ANCOVA at 0.05 level of significance. The findings of this study indicated that the three groups were equivalent or homogeneous prior to the application of the experimental treatment. The three groups also recorded significant improvement in their achievement in physics after being exposed to the experimental treatments. However, the students that were exposed to the self-instructional print media (whether independently or conjointly with the conventional teaching method) significantly outshone their counterparts that were taken through the conventional teaching method alone. Based on these findings, secondary school physics teachers were admonished to embrace the use of self-instructional print media to promote effective and efficient teaching and learning of Physics. They were also encouraged not to completely abandon the use of the conventional teaching method.